Implementasi Manajemen Sumber Daya Manusia Tenaga Pendidik SMA IT Ar Raihan di Kota Bandar Lampung - Yetri, Yetri; Fauzan, Ahmad; Noviyanti, Endah Nurul (El-Idare, 2022)
Human resource management will achieve effective and optimal results when carried out using appropriate and good procedures, one of which is planning. The purpose of human resource management is to organize and manage high-quality, reliable, qualified, productive, and professional human resources. This research uses a qualitative descriptive approach. Data collection is conducted through interviews, observations, and documentation. The data analysis used in this research involves data reduction, followed by presentation in the form of descriptions, and verification through drawing conclusions. The results of this research indicate that the implementation of planning and recruitment of employees in the implementation of human resource management for educational personnel at SMA IT Ar Raihan in Bandar Lampung City is carried out by first evaluating the number of educational personnel needed at SMA Ar-Raihan Bandar Lampung. Once the number is determined, announcements are made through various mass media, including newspapers.